2023
DOI: 10.1002/slct.202203630
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Sensor Based on Carbon Quantum Dots and Ionic Liquids for Selective Detection of Dopamine

Abstract: Dopamine (DA) as a neurotransmitter has a pivotal role in the central nervous system. Because of altered levels of DA in various neuroscience diseases, development of a quick, sensitive, and simple analytical approach to determine DA in biological fluids could be very applicable. In this research, a novel electrochemical sensor based on a carbon paste electrode (CPE) modified with ionic liquid (IL) and carbon quantum dots (CQDs) for measuring DA with uric acid and ascorbic acid was developed. IL and CQDs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…CD-based nanosystems have gained signicant attentions in recent years due to their distinctive structures and properties, which make them potential materials for biomedical applications. 75,76 CDs offer several advantages that make them ideal candidates for TE-RM applications, including low toxicity, exceptional biodegradability, biocompatibility, mechanical strength, antimicrobial characteristic, and biomineralization as well as their application in real-time tissue monitoring and visualization. 77,78 It has been indicated that the hydrogels incorporating CDs show enhanced cell proliferation and migration within scaffolds, higher osteogenic differentiation, increased tissue granulation, and collagen deposition during the tissue regeneration process.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…CD-based nanosystems have gained signicant attentions in recent years due to their distinctive structures and properties, which make them potential materials for biomedical applications. 75,76 CDs offer several advantages that make them ideal candidates for TE-RM applications, including low toxicity, exceptional biodegradability, biocompatibility, mechanical strength, antimicrobial characteristic, and biomineralization as well as their application in real-time tissue monitoring and visualization. 77,78 It has been indicated that the hydrogels incorporating CDs show enhanced cell proliferation and migration within scaffolds, higher osteogenic differentiation, increased tissue granulation, and collagen deposition during the tissue regeneration process.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…TEM has a high resolution of 0.1 to 0.2 nm, and it is used to determine the particle size and detailed morphology of nanomaterials. [52] The particle size of CQDs is below 10 nm; therefore, TEM can be used to determine their morphology, fine structure, crystalline properties, etc. For instance, Nguyen et al demonstrated spherical N-doped CQDs with size ranging from 1.78 to 6.50 nm graphite lattice d-spacing of 0.22 nm, known as interlayer spacing (Figure 3).…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…TEM has a high resolution of 0.1 to 0.2 nm, and it is used to determine the particle size and detailed morphology of nanomaterials [52] . The particle size of CQDs is below 10 nm; therefore, TEM can be used to determine their morphology, fine structure, crystalline properties, etc.…”
Section: Carbon Quantum Dots (Cqds)mentioning
confidence: 99%
“…Catechol (CC) is one of the typical phenolic compounds, which can cause a threat to human health even at very low concentrations and is therefore listed as a Group 2B carcinogen [4–6] . Generally, people exposed to CC may have to face acute health problems such as a rise in kidney/liver function, myeloid leukemia, and also the central nervous system [7,8] …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Generally, people exposed to CC may have to face acute health problems such as a rise in kidney/liver function, myeloid leukemia, and also the central nervous system. [7,8] Generally, in a polluted environmental system, CC coexists with other chemical species with low oxidation potentials. Therefore, accurate and reliable detection of CC from interference is necessary for practical application.…”
Section: Introductionmentioning
confidence: 99%